Modeling of structural and functional disorders of connective tissue of periodontal rats - V. N. Gorokhivsky; S. A. Schnaider; E. K. Tkachenko (Kazimierz Wielki University, 2017)
The purpose is to study the structural and functional state of the connective tissue of the periodontal rats under the conditions of periodontitis modeling by the administration of lidase. The experiment was carried out on 13 female rats 1 month age. 1st group - intact (5 individuals). In Group 2, rats were modeled on experimental periodontitis. The duration of the experiment was 55 days. As a result of subgingival injection of lidase, an experimental model of periodontitis was reproduced, which caused structural and functional disruption of the connective tissue of periodontium in rats.